Language Planning at Indonesian Pesantren and its Influence on Foreign Language Skills of Students “Pesantren Darul Muttaqin and Wali Tanduran as Role Model”: English - Saepul Anwar; Siti Khumairotuzzahra; Fadhel Akbar Ahmadi Usman (Universitas Djuanda, 2026)
This study examines language planning in Indonesian Islamic boarding schools (pesantren) and its influence on students’ Arabic language acquisition by comparing the modern Pesantren Darul Muttaqin in Tangerang and the traditional Pesantren Wali Tanduran in Pekalongan. Drawing on sociolinguistic perspectives on language planning and multilingual education, it investigates how institutional language policies, teaching practices, and learning environments shape students’ language proficiency. A qualitative descriptive approach was employed through classroom observations, semi-structured interviews, and document analysis conducted between November and December 2017. The participants included 8 language teachers (ustadzs) and their students. The findings reveal contrasting language planning models. Darul Muttaqin adopts an acquisition-oriented policy that promotes communicative competence through language immersion, memorization, discussions, vocabulary drills, language clubs, and the compulsory daily use of Arabic. This approach enhances students’ speaking and listening skills in Arabic but provides less support for grammatical accuracy and textual comprehension. In contrast, Wali Tanduran prioritizes mastery of kitab kuning through grammar-translation methods, memorization of classical Arabic grammar, and teacher-centered instruction using local languages, particularly Javanese. This model strengthens students’ reading comprehension and grammatical analysis but offers limited opportunities for communicative practice and vocabulary development. The study also identifies code-switching, code-mixing, and first-language interference as common sociolinguistic features in both institutions. It concludes that effective language planning in pesantren should integrate communicative language use with grammatical and textual competence to achieve balanced Arabic language proficiency.